(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The paper considers the solution of the problem of optimal control of systems with distributed parameters, described by partial differential equations of elliptic type, as applied to oil fields. A qualitative analysis of the states of the system has been carried out by solving a boundary value problem in the class of generalized functions.